Uji Sitotoksik Ekstrak Etanol Daun Bidara Arab (Ziziphus Spina-Christi L.) terhadap Sel Kanker Payudara (T47D) Menggunakan Metode MTT Assay - Anisa Oktavia Putri Aurianto; Rina Nurmaulawati; Kuncara Natawaskita (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Breast cancer (T47D) is a type of cancer with the highest percentage of new cases and cause of death. Cancer treatment is usually done by surgery, chemotherapy, and radiotherapy. Cancer treatment has so far given undesirable effects such as nausea, vomiting, mouth ulcers, nail damage, and hair loss. Cancer treatment has adverse effects, thus triggering the development of alternative treatments derived from nature or plants as anticancer therapy. The Arabian Bidara plant (Ziziphus spina-christi L.) is a round-leafed plant with many thorns that can grow in tropical areas. In the leaves of the Arabian bidara (Ziziphus spina-christi L.) there are alkaloid compounds, saponins, flavonoids, tannins, phenolics, steroids, triterpionids that have properties as anticancer. This study aims to determine the anticancer activity of the ethanol extract of Arabian bidara leaves against breast cancer cells (T47D) using the MTT assay method. This study is an experimental laboratory study. Ethanol extraction of Arabian bidara leaves using the maceration method. Cytotoxic test using the MTT assay method in five concentration test groups 125; 62.5; 31.25; 15.625 and 7.8 µg / mL, then the absorbance was read using an elisa reader. Cytotoxic activity is expressed by the IC50 value. Based on the results of the study, it showed that the ethanol extract of Arabian bidara leaves was cytotoxic to T47D cells. The IC50 value obtained from the ethanol extract of Arabian bidara leaves was 2,574 µg / mL, including the very active category. From the research results, it can be concluded that the ethanol extract of Arabian bidara leaves has anticancer activity against T47D cancer cells.